Very Early Continence After Radical Prostatectomy and Its Influencing Factors - Theissen, Lena; Preisser, Felix; Wenzel, Mike; Humke, Clara; Roos, Frederik C.; Kluth, Luis A.; Becker, Andreas; Banek, Severine; Bodelle, Boris; Köllermann, Jens; Chun, Felix K. H.; Mandel, Philipp (Frontiers in Surgery, 2019)
Introduction & objectives: Surgical techniques such as preservation of the full functional-length of the urethral sphincter (FFLU) have a positive impact on postoperative continence rates. Thereby, data on very early continence rates after radical prostatectomy (RP) are scarce. The aim of the present study was to analyze very early continence rates in patients undergoing FFLU during RP. Materials & methods: Very early-continence was assessed by using the PAD-test within 24 hours after removal of the transurethral catheter. The PAD-test is a validated test that measures the amount of involuntary urine loss while performing predefined physical activities within 1h (e.g. coughing, walking, climbing stairs). Full continence was defined as a urine loss below 1g. Mild, moderate and severe incontinence was defined as urine loss of 1-10g, 11-50g and >50g, respectively. Results: 90 patients were prospectively analyzed. Removal of the catheter was performed on the 6th postoperative day. Proportions for no, mild, moderate and severe incontinence were 18.9, 45.5, 20.0 and 15.6%, respectively. In logistic regression younger age was associated with significant better continence (HR 2.52, p=0.04), while bilateral nerve-sparing (HR 2.56, p=0.057) and organ-confined tumor (HR 2.22, p=0.078) showed lower urine loss, although the effect was statistically not significant. In MVA, similar results were recorded. Conclusion: Overall, 64.4% of patients were continent or suffered only from mild incontinence at 24h after catheter removal. In general, reduced urine loss was recorded in younger patients, patients with organ-confined tumor and in patients with bilateral nerve sparing. Severe incontinence rates were remarkably low with 15.6%.